Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.
KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.10.1.780 2339240:27J8DKI6 2405685:AYFYMSM8

Teacher Professional Development and Student Literacy Growth: a Systematic Review and Meta-analysis - Basma, Badriah; Savage, Robert (Educational Psychology Review, 2018)
This systematic review explores the impact of teacher professional development (PD) on student reading achievement. The first part of the literature evaluates all available existing systematic reviews and meta-analyses of PD intervention studies. No quality reviews of PD and reading specifically (distinct from ‘attainment’) were found. There was a little overlap of studies in existing reviews. The second part of the systematic review focuses on the most recent intervention studies exploring PD and student reading achievement. The results of a meta-analysis of all high-quality studies are presented in the third part of the paper. This analysis showed no strong evidence of publication bias and an effect size for PD on student literacy of g = 0.225. This effect was moderated by the number of hours of PD whereby studies with fewer than 30 h of PD was significant for student reading outcomes (g = 0.367, p < 0.001) but more than 30 PD hours was not significant (g = 0.143, p > .05). Following a Weight of Evidence assessment, analysis showed that nearly all high-quality articles involved shorter PD. Weight of Evidence was a significant moderator, (g = 0.408, p < 0.001 for high-quality studies, g = 0.077, p > 0.5, n.s., for medium quality studies). Our review suggests that only high-quality studies of short teacher PD currently provide evidence of impact on student’s reading achievement.
shortDOI: 10/ghgn5t KerkoCite.ItemAlsoKnownAs: 10.1007/s10648-017-9416-4 10/ghgn5t 2405685:9XT28XJI
Keywords: C: International

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
EdTechHub.Copy: 2129771:3IIW96ZB shortDOI: 10/gftrqf KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 10/gftrqf 2129771:3IIW96ZB 2339240:AUEREUTT 2339240:NNWXI67C 2339240:QWI89XDJ 2339240:X37484JK 2405685:37II7RPP 2405685:4PBTS4CP 2405685:5LADY8ET 2405685:L36BGXMK 2405685:PT6BTPEC
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Teachers of Refugees: A Review of the Literature - Richardson, Emily (Education Development Trust, 2018)
The United Nations High Commissioner for Refugees (UNHCR) estimates that 65.6 million people are forcibly displaced, having either crossed national borders or become internally displaced within their own countries. Of this estimate, over 22.5 million are refugees. Over half of the world's refugees are children. With an average length of displacement of approximately 20 years, the majority of these children will spend their entire childhoods away from home. Refugee children have limited access to basic social services like healthcare and education. Given the length of their displacement, generations of refugee children throughout the world could miss out on education altogether. Numerous studies show that the teacher is the most important in-school factor affecting the quality of education, particularly in refugee contexts, where the teacher is sometimes the only resource available to students. In refugee contexts where infrastructure and resources are limited, the role of the teacher is particularly important to the quality of education. However few studies to date have examined the role of teachers in refugee contexts. With more literature focusing on refugee children and youth, little is known about who the teachers of refugees are and how they are recruited, trained, retained, compensated and managed in their contexts. Importantly, there is little research on national teachers who are teaching refugee children; rather, much of the available literature focuses on refugee teachers – that is, teachers who are also refugees. In addition, this lack of literature on teachers of refugees hinders our understanding not only of their needs but also of 'how refugees can contribute to education in their host countries and (eventually) to their home countries'. The purpose of this literature review is to survey policies, practices and debates that governments and their partners must navigate to provide education for refugee populations, and the strategies they have used to select and manage teaching forces. The review analyses findings from the main literature on teachers of refugees according to the following themes: (1) recruitment, certification and selection of teachers; (2) teacher preparation and development; (3) teacher remuneration and incentives; and (4) teacher retention. In addition, for each of these themes, this review highlights the salient gaps in the research and suggests an agenda for further research. [Co-written with Leonora MacEwen and Ruth Naylor.]
Publication Title: Education Development Trust KerkoCite.ItemAlsoKnownAs: 2339240:KDEC9GDD 2405685:B3J76PXB
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_supporting educators

Teacher Professional Development around the World: The Gap between Evidence and Practice - Popova, Anna; Evans, David K.; Breeding, Mary E.; Arancibia, Violeta (World Bank, 2018)
shortDOI: 10/ghgngf KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8572 10/ghgngf 2339240:XS7TPHW4 2405685:RJX4M8AM 2405685:SQ5CWK8Q 2486141:U6AFHNPF
Keywords: C:Low- and middle-income countries

The Effect of Teacher Coaching on Instruction and Achievement: A Meta-Analysis of the Causal Effect - Kraft, Matthew A.; Blazar, David; Hogan, Dylan (Review of Educational Research, 2018)
Teacher coaching has emerged as a promising alternative to traditional models of professional development. We review the empirical literature on teacher coaching and conduct meta-analyses to estimate the mean effect of coaching programs on teachers’ instructional practice and students’ academic achievement. Combining results across 60 studies that employ causal research designs, we find pooled effect sizes of 0.49 standard deviations (SD) on instruction and 0.18 SD on achievement. Much of this evidence comes from literacy coaching programs for prekindergarten and elementary school teachers. Although these findings affirm the potential of coaching as a development tool, further analyses illustrate the challenges of taking coaching programs to scale while maintaining effectiveness. Average effects from effectiveness trials of larger programs are only a fraction of the effects found in efficacy trials of smaller programs. We conclude by discussing ways to address scale-up implementation challenges and providing guidance for future causal studies.
shortDOI: 10/ggjrhd KerkoCite.ItemAlsoKnownAs: 10.3102/0034654318759268 10/ggjrhd 2339240:94ATJ2KM 2339240:L9J24WV4 2339240:Q2UV8HVZ 2339240:Y3AHBV5R 2405685:2CWW72YN 2405685:3DXSV98B 2405685:6L7LJIMQ 2405685:JXICF3W3 2405685:KJDH8RVK 2405685:R4WDE3P4 2534378:9LCRTTXK
Keywords: C:High-income countries; C:United States; ___working_potential_duplicate; effect size; experimental design; meta-analysis; professional development; school/teacher effectiveness; teacher education/development

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:CNU2GKRL 2339240:KPPU5Z99 2339240:RNRNDVLK 2339240:S2XT5FSG 2339240:UYNN98AQ 2339240:Z8QK9TIS 2405685:4JNZ9RRF 2405685:58SRHUVT 2405685:CF2KPK7I 2405685:DJG72BUZ 2405685:FXXS4882 2405685:LW3BSKJ4 2405685:ZEBNC5TV 2534378:6GQU9R37 2534378:ARJJXBIL 2534378:TQ4YR37L 2534378:WSS9V2GJ 2534378:XIMVL4RJ
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC; Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UFXME9DD
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UFXME9DD
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

MOOCs as an alternative for teacher professional development: examining learner persistence in one Chinese MOOC - Wang, Qiong; Chen, Bodong; Fan, Yizhou; Zhang, Guogang (Peking University, 2018)
Massive Open Online Courses (MOOCs) have developed into a significant international movement, showing great promise in addressing equity, quality, and efficiency issues in global education. To date, many MOOCs have been developed specifically for teacher professional development (TPD). In this regard, an important empirical question remains to be addressed: How and to what extent can MOOCs support equity, quality, and efficiency in teacher professional development? To help fill this knowledge gap, this study, conducted from 2014 to 2016, focused on persistent teacher-learners in a TPD MOOC that was offered for seven consecutive rounds by the X-Learning Center of Peking University. The study found that more than 15% of the 105,383 teachers who enrolled in this MOOC were persistent teacher-learners, defined as learners who enrolled in multiple rounds. Data analysis showed that these persistent teacher-learners had diverse motivations for re-enrollment, including refreshing conceptual understanding, achieving higher scores, earning course certification, and discussing practical problems. The study also found that the persistent teacher-learners developed self-regulated learning skills in the course of multiple rounds of the MOOC and showed significantly higher learning achievement than one-time enrollees. Qualitative and quantitative analysis of both clicklog data and interview data revealed additional insights into the persistent teacher-learners’ learning within the MOOC and their real-world teaching practice beyond the MOOC. Overall, this study contributes to an improved understanding of the potential of MOOCs as an alternative TPD delivery mode in developing countries and sheds light on the future design of effective TPD through MOOCs.
Publisher: Foundation for Information Technology Education and Development, Inc.(FIT-ED) KerkoCite.ItemAlsoKnownAs: 2339240:8MN7IEZ9 2405685:3UKER6KZ 2405685:S4HRXBMD 2534378:KW6CG8KS 2534378:WIIQZEB5
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425977; __finaldtb; tpdsysrev_potential_duplicate; ⛔ No DOI found

Characteristics of effective teacher professional development: what we know, what we don’t, how we can find out - Sims, Sam; Fletcher-Wood, Harry (2018)
Several influential reviews and one meta-review have converged on the position that teacher professional development (PD) is more effective when it is: sustained, collaborative, subject-specific, draws on external expertise, has buy-in from teachers and is practice-based. This consensus view has now been incorporated in government policy and official guidance in several countries. Despite this, several recent PD programmes incorporating these characteristics have failed to have any detectable impact on pupil attainment. This article reviews the evidence underpinning the consensus, arguing that the reviews on which it based are methodologically flawed because they employ inappropriate exclusion criteria and depend on an invalid inference method. The consensus view is therefore likely to be inaccurate. Researchers would make more progress on identifying characteristics of effective professional development by looking for alignment between evidence from basic research on human skill acquisition and features of rigorously-evaluated PD interventions.
KerkoCite.ItemAlsoKnownAs: 2339240:2VB6UKTN 2405685:75VHL4AH 2405685:UH59JRDH
Keywords: C:International; CitedIn:OER4Schools-HHH3-A; ⛔ No DOI found

Pakistani Teachers' Professional Learning Experiences: Comparing Face-to-Face versus Online Learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 10/gj37jn 2339240:J3T4EMAA 2405685:TIQ5LA4J 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101887305?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 2405685:XI6TS4S3 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101887305?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 2405685:5TV4QEFU 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
KerkoCite.ItemAlsoKnownAs: 2339240:FCJF68RN 2405685:HQE8MXWS
Keywords: ⛔ No DOI found

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2018.1483265 2405685:FP425A4V
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

The Teachers’ Portal as a tool for teachers’ professional development in Bangladesh: Facilitating nationwide networking and digital multimedia content for 40,000 schools - Hansson, H; Sultana, S; Sarwar, A; Ahmed, F; Uddin, R; Saha, P; Islam, G; Islam, M (International Journal of Education and Development using ICT, 2018)
The Teachers’ Portal (teachers.gov.bd) is an online platform for Bangladeshi teachers designed to store and retrieve digital educational contents of different subjects useful for classroom teaching and students’ learning. The portal also facilitates professional networking among teachers across the country. This study aims to find out the benefits of using this Portal and associated challenges from teachers’ perspective. Following a mixed methods research approach Teachers, head teachers, teacher educators from primary, secondary, madrasa and vocational educational institutions and specialists on teachers’ Portal (N=410) were interviewed and consulted for the study. Telephone interviews, online surveys, Key Informant Interviews (KII), Focused Group Discussions (FGD), Face-to-Face interviews, and large consultative workshops were used to collect data. The results suggest that teachers are motivated to use the Portal as its contents stimulate students’ creativity and encourage students’ active participation in classrooms learning. Besides, it empowers teachers in a number of ways. However, internet connectivity, slow Internet speed, power failure, technical issues, high cost of Internet and unavailability of equipment are found as major challenges. In short, the Teachers’ Portal is a key driver for changing Bangladeshi education and preparing the young generation with quality education.
KerkoCite.ItemAlsoKnownAs: 2339240:YUIF5MMJ 2405685:ZSXBG9LT
Keywords: ⛔ No DOI found

Enhancing the teaching skills of the multi-grade teachers through lesson study - Thephavongsa, Souphanh (International Journal of Learning, Teaching and Educational Research, 2018)
Teaching in the multi-grade class is more difficult than mono-grade for teachers, however, multi-grade teaching was defined as the best strategy to achieving access to Education For All (EFA) of children especially those from rural areas. Teachers have been working diligently but unmethodical in their classroom. This study aimed to improve and enhance the teachers' professional skills which they have been facing in the classroom through the Lesson study and discuss why most of the teachers did not like to prepare and/or develop lesson plans. There were 100 participants who teach in the multi-grade schools in the Salavan district. The results represented that pre-test scores and post-test scores from two of training groups were significantly different and found that most of teachers do not usually prepare lesson plans. The research findings also determined that a Lesson study can be beneficial to enhance the development the teachers' professional skills.https://doi.org/10.26803/ijlter.17.4.5
Number: 4 KerkoCite.ItemAlsoKnownAs: 10.26803/ijlter.17.4.5 2339240:UR5ZQL62 2405685:GB9ETR4N
Keywords: Development a lesson plan; Lesson study approach; Multi-grade class; Multi-grade teaching; Training Multi-grade teachers; ⛔ No INSPIRE recid found

Investigating effects of using digital video in teacher training in Cambodia - Lok, Leandra; Schellings, Gonny; Brouwer, Niels; Den Brok, Perry (Journal of Technology and Teacher Education, 2018)
While research has shown that video can be an effective tool in the professional learning of teachers in industrialized countries, it is unknown whether this is also true for other countries with distinctive cultural, political, and historical contexts, such as Cambodia. This paper presents results from a study which examined the effectiveness of using video to introduce student-centered teaching to teachers in Cambodia. The training consisted of collaboratively watching and discussing videos of teaching practices. A 2x2 design was used, varying group conditions (team versus pair) and relevance of the material (model video versus action video). The findings indicated that although it was not possible to determine if there had been changes in teacher behavior, using video had led to an increase in teachers' perceived knowledge of student-centered teaching, especially for the team and the model video conditions.
Publisher: Association for the Advancement of Computing in Education, P.O. Box 1545, Chesapeake, VA 23327 KerkoCite.ItemAlsoKnownAs: 2405685:DBMD28PC 2534378:5IAKXKPQ 2534378:INDI72PC 2534378:W5INGKSD 2534378:ZPX4ANVW
Keywords: Active Learning; Behavior Change; Cambodia; Cultural Context; ERIC; Current Index to Journals in Education (CIJE); Education–Computer Applications; Faculty Development; Foreign Countries; Instructional Effectiveness; Knowledge Base for Teaching; Learning; Mixed Methods Research; Questionnaires; Student Centered Learning; Studies; Teacher Attitudes; Teacher Behavior; Teacher education; Teachers; Teaching; Teaching Methods; Training; Video; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2095890; __finaldtb; ⛔ No DOI found

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Place: Cambridge Publisher: Cambridge University Press Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2084810389?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1017/S0958344017000349 2405685:WM42S327 2534378:59HFNMGI 2534378:A5Y5932K 2534378:EEFLCSXC 2534378:G3TW72LP
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction–CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics–Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Publisher: The Open University KerkoCite.ItemAlsoKnownAs: 2339240:HMVJWSZ2 2405685:4IUVXWK9
Keywords: ___working_potential_duplicate

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Publisher: The Open University KerkoCite.ItemAlsoKnownAs: 2339240:HMVJWSZ2 2405685:4IUVXWK9
Keywords: ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UNPAN57F 2534378:GVRULWW2 2534378:SQKD29GI
Keywords: _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Education management; _THEME: Open systems; _THEME: School management; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2426091; ___working_potential_duplicate; __finaldtb

An overview of e-learning in China: History, challenges and opportunities - Wang, Yan; Liu, Xuan; Zhang, Zhenhong (Research in Comparative and International Education, 2018)
The Chinese government has attached great importance to the development of e-learning since its emergence in the 1990s. As a consequence of the implementation of a series of policies, China has made significant achievements in the e-learning arena with respect to infrastructure construction, production of resources, academic education, non-academic training, and education for disadvantaged groups. However, due to the constraints of China’s traditional culture, information literacy, and educational mechanisms, challenges have emerged in the implementation of e-learning that need urgently to be addressed. As e-learning in China continues to grow, major research areas such as students’ and teachers’ perspectives on developments in e-learning, teachers’ pedagogical capacity and ongoing professional development in e-learning settings, and the production of more convenient and useful e-learning resources, are likely to be topics of continuing research interest.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/1745499918763421 2405685:5RZFNBJU 2534378:WASU4R5U
Keywords: Challenges; China; ICT in education; e-learning; professional development; successes

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 2339240:W6C7ZW2X 2405685:53C9AZ8Q 2405685:RIK9NWV4 2534378:E5TCHLS4 2534378:QFTE8W6H
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 2339240:W6C7ZW2X 2405685:53C9AZ8Q 2405685:RIK9NWV4 2534378:E5TCHLS4 2534378:QFTE8W6H
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Emerging fundamental issues of teacher education in Tanzania: a reflection of practices - Mgaiwa, Samson J (Educational Process: International Journal, 2018)
Quality of teachers is recognized as one of the critical dimensions for promoting student learning in schools. However, in Tanzania there are several emerging issues that affect teacher education and teachers, and as a result affect students’ learning. The existing corpus of literature indicates a death of studies on the systematic understanding of issues that affect teacher education in Tanzania, especially at a time when education across the world is encountering a number of challenges. Employing documentary review and interviews as data collection methods, this paper attempts to analyze the emerging issues affecting teacher education in Tanzania. Employing the Teacher Education Model for the 21st Century, the paper identified five major issues affecting teacher education namely; lack of specific policies for teacher education, lack of continuing professional development, lack of an autonomous teacher regulatory body, inadequate ICT and teacher education, and poor quality of candidates joining teacher education. Generally, the findings indicate that teacher education is not effectively planned in terms of policy imperatives to meet the contemporary professional demands for 21st century education in Tanzania, and beyond. Finally, conclusions and certain recommendations which take a futuristic perspective in preparing 21st century teachers are offered.
Place: Kutahya Publisher: Universitepark, Co. Ltd. Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2377711234?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.22521/edupij.2018.74.3 2339240:5CD78LSE 2405685:9MDTIC8U 2534378:6CREM8X4 2534378:Q89SIFIE
Keywords: 21st century; Education; Learning; Tanzania; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095912; __finaldtb; students’ learning; teacher education; teachers

Effectiveness of Teachers’ Guides in the Global South: Scripting, Learning Outcomes, and Classroom Utilization - Piper, Benjamin; Sitabkhan, Yasmin; Mejia, Jessica; Betts, Kellie (RTI Press, 2018)
This report presents the results of RTI International Education’s study on teachers' guides across 13 countries and 19 projects. Using quantitative and qualitative methods, we examine how teachers’ guides across the projects differ and find substantial variation in the design and structure of the documents. We develop a scripting index so that the scripting levels of the guides can be compared across projects. The impact results of the programs that use teachers’ guides show significant impacts on learning outcomes, associated with approximately an additional half year of learning, showing that structured teachers’ guides contribute to improved learning outcomes. During observations, we find that teachers make a variety of changes in their classroom instruction from how the guides are written, showing that the utilization of structured teachers’ guides do not create robotic teachers unable to use their own professional skills to teach children. Unfortunately, many changes that teachers make reduce the amount of group work and interactivity that was described in the guides, suggesting that programs should encourage teachers to more heavily utilize the instructional routines designed in the guide. The report includes a set of research-based guidelines that material developers can use to develop teachers’ guides that will support effective instructional practices and help improve learning outcomes. The key takeaway from the report is that structured teachers' guides improve learning outcomes, but that overly scripted teachers' guides are somewhat less effective than simplified teachers' guides that give specific guidance to the teacher but are not written word for word for each lesson in the guide.
shortDOI: 10/ggjrfk KerkoCite.ItemAlsoKnownAs: 10.3768/rtipress.2018.op.0053.1805 10/ggjrfk 2339240:G6QUKYB2 2405685:8N3DSXF9 2405685:BX25H7CF 2405685:NLYSQ2ZG 2534378:AJ5Q28IL

USAID/Madagascar impact evaluation of the Mahay Mamaky Teny (MMT) project - Moussa, Wael; Cao, Yvonne; Louge, Nathalie (United States Agency for International development, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:57KZZLLD 2405685:DXY44ZMG

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason; Thornton, Rebecca L. (SSRN Electronic Journal, 2018)
shortDOI: 10/ghgn5h KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3002723 10/ghgn5h 2405685:NY5IKG96
Keywords: _C:Australia AUS; _C:Chad TCD; _C:Ecuador ECU; _C:India IND; _C:Kenya KEN; _C:Mexico MEX; _C:Spain ESP; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:scheme:1

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem–the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity–and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints–most of them beyond the scope of action of teachers and students and not approached by previous research–hindering the integration of mathematical modelling in current secondary schools.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101593199?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s11858-017-0907-z 2339240:4YXECT54 2405685:2GGB99HT 2405685:6B4BREQ8 2534378:8BWRCH2S 2534378:RTGC7399
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

An Evaluation of ELLN Digital: Technology-Supported Teacher Professional Development on Early Language, Literacy, and Numeracy for K-3 Teachers - Oakley, Grace; King, Ronnel; Scarparolo, Gemma (Digital Learning for Development, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:KW3JXUFD 2405685:QDANF5S7
Keywords: ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

How to Improve Teaching Practice? Experimental Comparison of Centralized Training and In-classroom Coaching - Cilliers, Jacobus; Fleisch, Brahm; Prinsloo, Cas; Taylor, Stephen (Research on Improving Systems of Education (RISE), 2018)
We experimentally compare two modes of in-service professional development for South African public primary school teachers. In both programs teachers received the same learning material and daily lesson plans, aligned to the ofﬁcial literacy curriculum. Pupils exposed to two years of the program improved their reading proﬁciency by 0.12 standard deviations if their teachers received centralized Training, compared to 0.24 if their teachers received in-class Coaching. Classroom observations reveal that teachers were more likely to split pupils into smaller reading groups, which enabled individualized attention and more opportunities to practice reading. Results vary by class size and baseline pupil reading proﬁciency.
shortDOI: 10/ghgnff KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2018/024 10/ghgnff 2405685:WYIY3SSM
Keywords: C: South Africa

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:2M2HXSJN 2405685:SNDDADWB 2405685:SNTV94NA 2534378:7FFHYISA 2534378:ASX6DAFV 2534378:WH9M9DZM
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

Teachers in Tatweer Primary Schools in Saudi Arabia and Interactive White Boards: Towards a Professional Development Model - Alghamdi, Azzah Hamed (Durham University, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:EC9JYRN8

Understanding factors affecting primary school teachers’ use of ICT for student-centered education in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Takada, Jun-ichi (2018)
The past two decades witnessed continuous uptake of ICT in education, and the importance of teachers’ beliefs for adopting ICT in education was revealed in the context of educational change. In recent years, the Mongolian educational system has placed more emphasis on student-centered education and the use of ICT in teaching and learning. Teacher training has become a local responsibility under the Education Master Plan (Government of Mongolia, 2006), New Education Standard and Core Curriculum which focus on the introduction of ICT into education and the implementation of student-centered education (Asian Development Bank, 2008; Ministry of Culture Education and Science, 2014). Despite the growing interest in using ICT for student-centered education, a limited number of studies exist in Mongolia to understand primary school teachers’ perception on use of ICT for student-centered education. This study aims to understand the factors affecting teachers’ perceptions on use of ICT for student-centered education. Based on Fullan’s educational change theory, the analysis through multiple linear regression and focus group discussion was conducted on 838 primary school teachers in Mongolia which found that teacher’s professional competency and perceived benefits on use of ICT are significant factors affecting teachers’ perceptions on use of ICT tool for student-centered education. Furthermore, teacher’s professional competency, perceived benefits on use of ICT and teacher cooperation are affecting teachers’ perceptions on use of digital contents for student-centered education.
KerkoCite.ItemAlsoKnownAs: 2339240:J6FMCEMP 2405685:UJYVC9Z6
Keywords: ⛔ No DOI found

Using instructional video to improve awareness of scientific approach in science classroom - Susantini, Endang; Faizah, Ulfi; Yonata, Bertha; Kurniasari, Ika; Suryanti (Asia-Pacific Forum on Science Learning and Teaching, 2018)
Instructional videos have been developed to engage pre-service teachers to learn how to teach scientific approach in science classroom. This study aimed to improve preservice teachers' awareness of scientific approach in science classroom through instructional video along with their responses. Thirty two pre-service science teachers from Universitas Negeri Surabaya, Surabaya, Indonesia, participated in this study and observed two different instructional videos using video-analysis worksheet supplemented by the supervisor. In response to the instructional video, results showed that pre-service teachers noticed well about application of scientific approach in inquiry-based teaching and cooperative learning models. Pre-service teachers also showed positive views about the instructional videos and became a reflection for their own future teaching actions and practices. Supplementation of the video-analysis worksheet during the implementation and peer-discussion among preservice teachers can be used to improve pre-service teachers' awareness as well as to provide clear exemplary about how to integrate scientific approach at each phase of inquiry-based teaching and cooperative learning models. This study implies that the present instructional videos and followed-up video-analysis task are adequate to facilitate pre-service teachers to understand what to do in actual classroom in terms of applying scientific approach as envisioned by Indonesia curriculum reform.
Publisher: Hong Kong Institute of Education, 10 Lo Ping Road, Tai Po, New Territories, Hong Kong KerkoCite.ItemAlsoKnownAs: 2339240:BN9QC37H 2339240:LBY74V36 2405685:DVSNFSAI 2405685:S42A5QRW 2534378:JX3N56UR 2534378:JZI7NCMR 2534378:WYRLILRV
Keywords: Active Learning; Biology; Chemistry; Classrooms; Cooperative Learning; Cooperative learning; Curricula; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Foreign Countries; Higher Education; Hypotheses; Indonesia; Inquiry; Inquiry method; Instructional Material Evaluation; Mathematics; Models; Pedagogy; Preservice Teacher Education; Preservice Teachers; Professional development; Science Instruction; Science Teachers; Science education; Sciences: Comprehensive Works; Scientific Methodology; Student Attitudes; Students; Teacher education; Teaching Methods; Teaching methods; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2097317; __finaldtb; ⚠️ Invalid DOI; ⛔ No DOI found